Transforming finance in the Middle East and North Africa - Arezki, Rabah,Senbet, Lemma W. (World Bank Group, Middle East and North Africa Region, Office of the Chief Economist, 2020)
This paper argues for a transformation of finance to support the economic and social transformation of the Middle East and North Africa. The paper first documents the existing financial system in the region. The system is heavily skewed toward banking, relative to non-banking services, such as stock and corporate bond markets, with significant heterogeneity across countries. Second, the paper discusses the stance of macroeconomic policy in the region, which has had important implications for the destination, profitability, and quality of bank lending and the limited evolution of the financial system. Third, the paper explores the impact of technology on financial development, with particular attention to prospects for the development of fintechs. Entrenched incumbency of banks has limited the role of non-bank operators in fostering market contestability and fintech development. The paper is a call to the authorities and policy makers in the Middle East and North Africa to break with the status quo and business as usual. It underscores the need for a
10.1596/1813-9450-9301
Keywords: Graue Literatur; financial system; macroeconomic policy; growth; Middle East and North Africa